KAJIAN TEORI ANALISA PENGGUNAAN SURYA PANEL SEBAGAI KEBUTUHAN LISTRIK PADA KAPAL NELAYAN DI PANTAI UTARA TEGAL JAWA TENGAH KAJIAN TEORI ANALISA PENGGUNAAN SURYA PANEL SEBAGAI KEBUTUHAN LISTRIK PADA KAPAL NELAYAN DI PANTAI UTARA TEGAL JAWA TENGAH - Teguh Purnomo (Jurusan Teknik Mesin, Universitas Halu Oleo, 2021)
fishing activities carried out by fishermen. Fishermen need certain types of vessels to support the activities. In the operation of the ship, fishermen need fossil fuels and the use of electricity on board the ship. But not infrequently fishermen often have an imbalance problem between the operational costs of the ship and the profit. From the observations, the cost of recharging accu battery and the purchase of diesel fuel became the main obstacles. the author observes the need for the use of electricity and fuel is the main thing on board, one of which is for the use of lighting, drying and driving the ship. In addition, the depletion of fossil energy resources is also a major concern. To solve the problem, an alternative replacement is needed. The development of renewable energy resources through solar energy can be planned as to address the problem in question. With solar panel technology installed on board fishing boats, the need for electricity use and replacement of diesel fuel can be helped. This technology converts solar energy into electrical energy through solar cells which are then stored in the accu battery for the needs of electricity sources on fishing boats.